Study of the role of Fe based catalysts on the growth of B-doped SWCNTS synthesized by CVD - Daothong S. (2014)
Although boron doped multi-walled nanotubes have been synthesized by chemical vapor deposition (CVD) methods, the synthesis of single-walled species was achieved only recently. In comparison to their carbon counterparts synthesized by similar methods, these nanotubes grow in relatively low amounts due to several experimental difficulties. On the other hand, the use of iron containing catalysts supported in porous materials is one of the most efficient ways to produce single walled pristine carbon nanotubes and several methods have been proposed to enhance this growth. In this contribution we have studied the possibilities to enhance the growth of boron doped single-walled nanotubes using a triisopropyl borate nondiluted precursor in a high-vacuum CVD system. The catalyst composition and pretreatment, as well as the precursor-feed have been studied in detail. An additional study of the Raman response our material has been made in order to prove the implicit changes with electrons and phonons upon doping. © 2009 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.